Assessing the Presence of Natural Radioactive Isotopes in the Soils and Leaves and their Effects on Domestic Livestock of Atulya and Mtembur of Pokot North Sub-County, West Pokot County - Motum, M.; Lutta, S.; Lusweti , K.; Barasa, S. (Africa Environmental Review Journal, 2021)
Natural radioactivity from celestial sources and radioactive matter in the earth's crust is a source of constant radiation exposure to animals. The main contribution to external exposure comes from gamma-emitting radionuclides present in trace elements in the soil, mainly K-40, U-238 and Th-232 families. The levels due to the terrestrial background radiation are related to the types of rock from which the soils originate. This research investigated the absorbed dose and annual effective dose rate from radiations emitted by radionuclides from soil, leaves and cattle’s animal parts in West Pokot region, Kenya. Purposive sampling method was used to identify points for soil sampling where deformed domesticated animals are from. Soil samples collected samples were analysed using LB 200 Bequerel Monitor. Bones and skin parts were obtained from a slaughter house from the two regions and radioactivity analysis was done at the National Radiation Protection Board laboratory (Nairobi). Leaves samples which weighed less than 500g were analysed using a Ratemeter. Soil samples from Atulya had a higher mean activity concentration (300.00 ± 1.080) Bql-1 while the soil samples from Mtembur had the lower mean activity concentration (228.50 ±.645) Bql-1, these values were well above world average values. The mean activity for leaves were 57cpm and 56 cpm for Atulya and Mtembur respectively. Both animal parts had lower mean activity concentrations: 162.00 .913 Bql-1 for the skin 167.00 ± .816Bql-1 for the bones from West Pokot County. The results further showed elevated radioactive exposure in soils 0.561 mSv/y and leaves samples 0.573 mSv/y from Mtembur. Samples from Atulya also indicated high radioactive levels of 0.737 mSv/y in soil samples and 0.5835 mSv/y from leaves samples as compared to recommended minimum levels UNSCEAR. Domesticated cattle bones and skin collected from slaughter house indicated radioactivity of 0.4029 mSv/y. There was a significant difference (p≤0.05) in the levels of radiation in soil between Mtembur and Atulya according to T- test results (P=0.000, df=3, t=-41.288). There was a negative correlation in radiation activity levels between the soil and leaves and skin and leaves and bones found Mtembur and Atulya in West Pokot County. Evidently, animals in West Pokot County are exposed to harmful radiations leading to deformities like fragile limbs, misplaced organs and multiple organs. This leads to poor economic returns to the pastoral community. The study therefore recommends that a system should also be put in place to monitor radionuclides in major food commodities in order to reduce human exposure to radiation through consumption of animal products.